Boosting innovative work behavior on local branded fashion: The evidence from Indonesia - SETIAWAN, R; SURYANI, T; TIRSA, G; ELIYANA, A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article analyzes the role of psychological empowerment as an intervening variable on the relationship between transformational leadership and employees innovative work behavior (IWB). This research used a quantitative approach with a total of 100 employees from local branded fashion businesses in Indonesia to fill out the questionnaires. The sample was taken using a non-probability sampling technique. This study adds to innovative work behavior literature by empirically testing the mediating role of psychological empowerment on transformational leadership and innovative work behavior relationship. This study resolves the research gap between transformational leadership and innovative work behavior with the concept of psychological empowerment.